A longitudinal study of rural Bangladeshi children with long-term arsenic and cadmium exposures and biomarkers of cardiometabolic diseases. (15th February 2021) - Akhtar, Evana; Roy, Anjan Kumar; Haq, Md Ahsanul; von Ehrenstein, Ondine S.; Ahmed, Sultan; Vahter, Marie; Ekstrom, Eva-Charlotte; Kippler, Maria; Wagatsuma, Yukiko; Raqib, Rubhana
Abstract: There is growing interest in understanding the contribution of environmental toxicant exposure in early life to development of cardiometabolic diseases (CMD) in adulthood. We aimed to assess associations of early life exposure to arsenic and cadmium with biomarkers of CMD in children in rural Bangladesh. From a longitudinal mother-child cohort in Matlab, Bangladesh, we followed up 540 pairs. Exposure to arsenic (U–As) and cadmium (U–Cd) was assessed by concentrations in urine from mothers at gestational week 8 (GW8) and children at ages 4.5 and 9 years. Blood pressure and anthropometric indices were measured at 4.5 and 9 years. Metabolic markers (lipids, glucose, hemoglobin A1c, adipokines, estimated glomerular filtration rate (eGFR) were determined in plasma/blood of 9 years old children. In linear regression models, adjusted for child sex, age, height-for-age z score (HAZ), BMI-for-age z score (BAZ), socioeconomic status (SES) and maternal education, each doubling of maternal and early childhood U–Cd was associated with 0.73 and 0.82 mmHg increase in systolic blood pressure (SBP) respectively. Both early and concurrent childhood U–Cd was associated with diastolic (D)BP (β = 0.80 at 4.5 years; β = 0.75 at 9 years). Each doubling of U–Cd at 9 years was associated with decrements of 4.98 mg/dL of total cholesterol (TC), 1.75 mg/dL high-density lipoprotein (HDL), 3.85 mg/dL low-density lipoprotein (LDL), 0.43 mg/dL glucose and 4.29 units eGFR. Each doubling of maternal U–Cd was associated with a decrement of 1.23 mg/dL HDL. Both maternal and childhood U–As were associated with decrement in TC and HDL. Multiple comparisons were checked with family-wise error rate Bonferroni-type-approach. The negative associations of arsenic and cadmium with biomarkers of CMD in preadolescent children indicated influence of both metal(loid)s on fat and carbohydrate metabolism, while cadmium additionally influenced kidney function and BP. Thus, fewer outcomes were associated with U–As compared to U–Cd at preadolescence. Graphical abstract: Image 1 Highlights: Early signs of detrimental influence of metal(loid)s on fat metabolism in children. Early life cadmium exposure was associated with increased preadolescent blood pressure. Early life arsenic or cadmium exposure was associated with decreased plasma lipoproteins. Childhood cadmium exposure was inversely associated with kidney function (eGFR). Abstract : I n utero through early childhood exposure to arsenic and cadmium is linked with impaired fat and carbohydrate metabolism, while cadmium is additionally associated with reduced kidney function and increased blood pressure in preadolescent children in rural Bangladesh.